Optimization of Stock Portfolio of Value30 Index And Growth30 Index Using the Markowitz Model and Sharpe Model - Adrian Hengkenusa Kalebos; Dudi Rudianto (AIBPM Publisher, 2022)
This study aims to determine the results of optimizing stock portfolios on the Value30 and Growth30 indexes on the Indonesia Stock Exchange based on the Markowitz Model and Sharpe Model. There are seven stocks that are consistently listed on the Value30 index selected with the code ADRO, BJBR, ELSA, ITMG, PTBA, PTPP, UNTR and seven stocks that are consistently listed on the Growth30 index selected with the code ACES, BBCA, BBRI, CPIN, ERAA, TBIG , TOWR. The data is taken from the period January 2015 to December 2021. Using the Markowitz model on the Value30 index stock yields a return of 1.08% and a standard deviation of 8.02% (coefficient of variation/cv 7.426). Meanwhile, the Growth30 index stock yielded a return of 1.36% and a standard deviation of 4.46% (cv 3.279). Using the Sharpe model on the Value30 index stock yields a return of 2.23% and a standard deviation of 11.01% (cv 4.937). Meanwhile, the Growth30 index stock yielded a return of 1.54% and a standard deviation of 4.88% (cv 3.169). This study concludes that the Sharpe Model provide a more optimal investment return than the Markowitz Model for both the Value30 and Growth30 index stocks. Keywords: Index Growth30, Index Value30, Model Markowitz, Model Sharpe, Portfolio.